Pengaruh Kepemilikan Manajerial, Ukuran Perusahaan dan Leverage Terhadap Financial Distress - Gina Septiana; Pipi Agus Puspa Sari (Jurnal Ilmiah Pendidikan Scholastic, 2021)
Financial distress is a condition in which a company is facing a period of financial difficulty and conditions that occur before the company actually goes bankrupt. This study aims to obtain empirical evidence whether there is an effect of managerial ownership, company size and leverage on financial distress in companies listed on the Indonesia Stock Exchange for the period 2015 - 2019. The sampling technique uses purposive sampling method and is based on criteria. samples obtained from 9 companies. Data from financial reports are obtained from the IDX official website. The analysis method used is panel data regression analysis with the help of the E-Views 8 application. After doing the chow-test, it was decided to choose the fixed effect method. Financial distress on publicly listed companies on the IDX during the study period was only positively and significantly influenced by managerial ownership, firm size had no significant effect and leverage has a negative and significant effect.